To study the correlation of mean macular thickness using optical coherence tomography with distant and near visual acuity in patients of diabetic maculopathy - Arora, Sahil; Sachdeva, Abhishek; Goel, Tushar; Singh, Komal; Aggarwal, Mridu (International Journal of Research in Medical Sciences, 2018)
Background: to study the correlation of mean macular thickness using optical coherence tomography with distant and near visual acuity in patients of diabetic maculopathy. Methods: A prospective, single centre study was conducted on 50 eyes of diabetic patients, with Diabetic Retinopathy with CSME in which patients macular thickness was measured on Ocular Coherence Tomography using fast macular thickness scan. The unaided and best corrected visual acuity was measured in all patients using Snellens distant vision and Jaggers near vision charts. Results: A linear correlation between the OCT measured macular thickness and both the distance visual acuity and the near visual acuity. That means that for a given level of macular thickness, we can predict visual acuity for it. In our series correlation coefficient was 0.921 for distance visual acuity and 0.899 for near visual acuity. Although the correlation value is high in our study, we did find a range of visual acuities for a given range of macular thickness. For every 100 micron change in mean macular thickness, best corrected visual acuity (BCVA) changed 0.3 LogMAR units, for distance as well as for near. Conclusions: Macular thickness and visual acuities (distance as well as near) are strongly correlated but there can be variations. And a wide range of visual acuities is possible for a given degree of macular edema. Macular thickness though a strong predictor of visual acuity; other factors might also play a role in determining visual acuity for a particular patient.